IPTCOMKIT: Commercialization of Institute of Higher Learning Research Toolkit - Mohamad, Kamal (2010)
Even though many of research made by Institute of Higher Learning (IHL) researchers have received many awards from local events or international events, the rate of the commercialized products by IHL researchers is still low. Lack of information on how to commercialize research product is one of the causes for this to happen (Richard & Thursby, 2001). The purpose of this project is to build the IPT Commercialization Toolkit (IPTComKit), a toolkit which to guide IHL researchers to commercialize their research findings or results. IPTComKit provides a complete guide to commercialize based on a commercialization process model introduced by Saville and Norsaadah (2010a). The IPTComKit can provide information for steps to commercialize, the purpose of the steps, tasks needed to be followed, provide templates, and the outcome of every step.